How Indonesian Investment Law Positively Impacts the Environment for Foreign Businesses - Wanibe, Kenji Dustin; Vincent, Vincent; Putra, Moody Rizqy Syailendra (CV. Rayyan Dwi Bharata, 2025)
Indonesia, as one of the founding members of the Association of Southeast Asian Nations (ASEAN) and a member of the Group of Twenty (G20), possesses distinct advantages. Its sustained economic development, rapid investment growth, abundant natural resources, and expansive market have established its significant international presence, positioning it as a frontrunner among other ASEAN countries. As one of the most influential members among the ten ASEAN nations, Indonesia holds remarkable appeal for foreign investment and garners considerable attention in the investment sphere. This article employs methodologies including data analysis and literature review to concentrate on Indonesia’s investment laws, exploring potential risks within Indonesia’s investment environment and corresponding strategies for mitigation. The article also focuses on Indonesia’s domestic laws and Bilateral Investment Treaties (BITs) related to investment, outlining the framework of Indonesia’s investment legal environment by examining the risks, challenges, and benefits posed by Indonesia’s investment laws. The primary focus of this paper lies in dissecting the risks and challenges inherent in Indonesian investment laws while identifying pathways for resolution.